Examining the Impact on Married Couples' Earnings Distributions of Standardizing for Difference in Hours Worked - Mary Kilfoil (Luxembourg Income Study (LIS), 1999)
This paper examines the relationship between the distribution of average annual household pre-tax earnings and average annual household hours of market work for married couple households. The point of departure in this paper is the treatment of the variation in annual hours worked either over time within Canada or across countries. This paper adds to the literature explicit consideration of the differences in hours worked across households, either across countries or over time periods, by proposing an additional standardization of household earnings to account for differences in the number of hours worked across households.
Keywords: 330; Haushaltseinkommen; Freizeitverhalten; Hausarbeit; Kanada; Australien; Finnland; Niederlande; USA; Ehe